Bacterial degradation of palm olein in seawater and identification of some cultivable strains - Bhubalan K.,; Hui-Wan, R.A.C.; Renganathan P.,; Tamothran A.M.,; Ganesen S.S.K.,; Ghazali R., (Penerbit Universiti Kebangsaan Malaysia, 2019)
Palm oil transported in bulk through ocean can increase pollution risks due to accidental spillage or ship collision, especially the refined, bleached and deodorized (RBD) palm olein. Bacterial degradation of RBD palm olein in seawater was investigated as a preliminary finding on palm oil degradation by marine bacteria. The degradation of RBD palm olein was evaluated in seawater in shaken-flask cultures with different oil concentrations. Biochemical oxygen demand (BOD) in the seawater was determined based on changes in dissolved oxygen (DO) values before and at end of 5-day incubation. The concentrations of major fatty acid components in RBD palm olein before and after degradation were determined using gas chromatographyflame ionization detector (GC-FID). Isolated bacteria were screened for lipolytic activity using Spirit Blue Agar before molecular identification. The DO content reduced 20% over a 5-day incubation period and BOD value was determined to be 1.24 mg O2/L based on DO values. The concentrations of fatty acids, namely palmitic acid (C16:0), stearic acid (C18:0) and oleic acid (C18:1) decreased by 53%, 31% and 37%, respectively. The bacterial count increased from 980 CFU/mL during inoculation to 1.8 x 104 CFU/mL on day 5. Five phenotypically different bacterial strains (Pseudoalteromonas gelatinolytica, Staphylococcus haemolyticus, Vibrio harveyi and Vibrio alginolyticus) showed lipolytic activity. This study indicates that marine bacteria utilizes RBD palm olein as substrate, thus degrading it over time.